PLACE OF LEGAL TRANSACTIONS IN SYSTEM OF CIVIL LAW - Шишка, Роман Богданович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article deals with the confusion in the current acts of legislation and prospect of the legal transactions’ institution in the system of civil law with the full adaptation of Ukrainian’s civil legislation to the demands of EU countries’ legislation. Attention is drawn to the contradictions in the institution of transaction itself, its sub institutions, unconformity with the institution of commercial obligations and contracts. The author believes that the legislature should change the approach in favor of one justified and proven historically and stop the experiment.